2014
DOI: 10.1002/aic.14356
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic coating of silicate phosphor powder using atmospheric pressure dielectric barrier discharge plasma

Abstract: A stable superhydrophobic coating was successfully deposited on commercial silicate-based orange phosphor by using atmospheric pressure dielectric barrier discharge plasma with hexamethyldisiloxane (HMDSO) and HMDSO/toluene mixture as precursors. Owning to the good optical properties, the deposited film acts not only as a hydrophobic protective layer but also as an antireflection optical thin film capable of improving the phosphor photoluminescence efficiency. The plasma-polymerized film based on SiAOASi backb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…On the basis of the above discussions and results reported in the literature, [ 12,26,61,101,102 ] the predominant plasma‐chemical reaction pathway for the combined HMDSO activation reactions in plasma‐state polymerization can be proposed on the basis of electron impact yielding the film‐forming species, • (CH 3 ) 2 SiO • : (CH3)3SiOSi(CH3)3+normale (CH3)20.15emSiO+(CH3)3Si+ CH3+normale,…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the above discussions and results reported in the literature, [ 12,26,61,101,102 ] the predominant plasma‐chemical reaction pathway for the combined HMDSO activation reactions in plasma‐state polymerization can be proposed on the basis of electron impact yielding the film‐forming species, • (CH 3 ) 2 SiO • : (CH3)3SiOSi(CH3)3+normale (CH3)20.15emSiO+(CH3)3Si+ CH3+normale,…”
Section: Resultsmentioning
confidence: 99%
“…The aging time was reported to have a significant effect on WCA for the powder substrate coating [23]. Trinh et al [23] have reported that the WCA could increase by 15-40°within 30 days in the case of powder substrate coating.…”
Section: Coating Stability Testmentioning
confidence: 99%
“…Based on a brief analysis of XPS and FTIR, the process of decomposition of monomer was shown in reaction I [37]. During plasma discharge, argon is ionized by a dualfrequency power source at atmospheric pressure and it will [38]. It should be noted that reaction I is only the fundamental mechanism, and more detailed and complicated reactions simultaneously occur in the plasma system.…”
Section: Film Characterization Techniquesmentioning
confidence: 99%